La Migración Venezolana en Brasil: crisis humanitaria, la desinformación y aspectos regulatorios - de Oliveira, Antônio Tadeu Ribeiro (2019)
The political, social and economic crises that come affecting Venezuela, and intensified in the second half of the current decade, put international migration as an alternative to survival for about 2 million of Venezuelans, with Brazil being one among the many of the targets of these migrants. This serious situation eventually translates into a real humanitarian crisis. From that look, the purpose of this article, to understand these movements as forced labour migration, faced with the shortage of references, It was resorting to journalistic material, some results of statistical surveys conducted field and administrative records to get an overview about the trajectory and insertion of these immigrants in the target society, pointing out how the misinformation spread by local authorities, increased volumes of migratory flows, served to create a negative image of immigrants, generating some episodes of aggression. All this against a background of lack of coordination between the federated entities in the conduct of appropriate migration policies.